2021
DOI: 10.3390/plants10020369
|View full text |Cite
|
Sign up to set email alerts
|

Marine Organisms for the Sustainable Management of Plant Parasitic Nematodes

Abstract: Plant parasitic nematodes are annually responsible for the loss of 10%–25% of worldwide crop production, most of which is attributable to root-knot nematodes (RKNs) that infest a wide range of agricultural crops throughout the world. Current nematode control tools are not enough to ensure the effective management of these parasites, mainly due to the severe restrictions imposed on the use of chemical pesticides. Therefore, it is important to discover new potential nematicidal sources that are suitable for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Regarding nematicidal activity, the brown seaweed Padina concrescens showed the highest egg hatching inhibition of M. incognita (59%), followed by red seaweed Laurencia johnstonii (48%) and Sargassum horridum (43%). Previous experiments have shown that aqueous and methanolic extracts of brown and red seaweeds are more effective than those of green macroalgae on nematode egg hatching inhibition and nematicidal activity(Khan et al, 2015;Veronico & Melillo, 2021). Even though the seaweeds studied, in the investigation mentioned before, were collected in very different location compared to the seaweeds collected for this experiment, our results indicate the same tendency.…”
supporting
confidence: 71%

Evaluation of Baja Peninsula seaweeds against plant pathogens

González-Castro,
Rojas-Contreras,
Romero-Bastidas
et al. 2024
Preprint
“…Regarding nematicidal activity, the brown seaweed Padina concrescens showed the highest egg hatching inhibition of M. incognita (59%), followed by red seaweed Laurencia johnstonii (48%) and Sargassum horridum (43%). Previous experiments have shown that aqueous and methanolic extracts of brown and red seaweeds are more effective than those of green macroalgae on nematode egg hatching inhibition and nematicidal activity(Khan et al, 2015;Veronico & Melillo, 2021). Even though the seaweeds studied, in the investigation mentioned before, were collected in very different location compared to the seaweeds collected for this experiment, our results indicate the same tendency.…”
supporting
confidence: 71%

Evaluation of Baja Peninsula seaweeds against plant pathogens

González-Castro,
Rojas-Contreras,
Romero-Bastidas
et al. 2024
Preprint
“…The extracts and compounds from micro-and macroalgae are also effective against plant-parasitic nematodes that are responsible for the annual loss of 10-25% of worldwide crop production [92] (Table 4). Brominated diterpenes that were isolated from the marine red alga Jania rubens were effective against Allolobophora caliginosa [93].…”
Section: Nematocidal Actionmentioning
confidence: 99%
“…Like terrestrial plants, marine biodiversity may prove to be a promising source of safe nematicidal agents. [44] As Ceriops tagal was never tested for nematicidal potential, it was selected for evaluation of its activity against larvae of cyst nematode H. zeae. On extraction with petroleum ether, aerial parts of the plant afforded an extract (CTP), which displayed promising nematicidal activity after exposure for 72 h. It was subjected to bioassay directed isolation studies employing classical solventsolvent separation, affording petroleum ether soluble (CTP-S) and insoluble fractions (CTP-IN).…”
Section: Composition and Characterizationmentioning
confidence: 99%